John Dewey’s Concept of the Student - Simpson, Douglas (Canadian Journal of Education/Revue canadienne de l'éducation, 2001)
In this article, I have examined Dewey’s concept of the student through the lens of his poetry and prose to show that his poetry clarifies his prose. I have devoted special attention to a study of Dewey’s poetry to reveal his belief that students are more fragile than his prose suggests and that they need guidance in their desire for freedom to learn. His poetry also suggests that students need help to navigate society’s contradictory educational currents. Without such help, they will likely suffer damaging, permanent outcomes. L’article analyse, à travers les poèmes et la prose de Dewey, son concept de l’élève. Les poèmes de Dewey présentent l’élève comme étant plus fragile que ce que pouvait laisser supposer sa prose et comment il doit être guidé dans son désir de liberté dans l’apprentissage. La poésie de Dewey laisse entendre aussi que les élèves ont besoin d’aide pour trouver leur voie dans les courants éducatifs contradictoires de la société. Sans cette aide, ils risquent d’être affectés de manière permanente.